Alteration of the groove width of DNA induced by the multimodal hydrogen bonding of denaturants with DNA bases in its grooves affects their stability - Sarkar, Sunipa; Singh, Prashant Chandra (Biochimica et biophysica acta. General subjects, 2020)
Denaturants, namely, urea and guanidinium chloride (GdmCl) affect the stability as well as structure of DNA. Critical assessment of the role of hydrogen bonding of these denaturants with the different regions of DNA is essential in terms of its stability and structural aspect. However, the understanding of the mechanistic aspects of structural change of DNA induced by the denaturants is not yet well understood. In this study, various spectroscopic along with molecular dynamics (MD) simulation techniques were employed to understand the role of hydrogen bonding of these denaturants with DNA bases in their stability and structural change. It has been found that both, GdmCl and urea intrude into groove region of DNA by striping surrounding water. The hydrogen bonding pattern of Gdm+ and urea with DNA bases in its groove region is multimodal and distinctly different from each other. The interaction of GdmCl with DNA is stabilized by electrostatic interaction whereas electrostatic and Lennard-Jones interactions both contribute for urea. Gdm+ forms direct hydrogen bond with the bases in the minor groove of DNA whereas direct and water assisted hydrogen bond takes place with urea. The hydrogen bond formed between Gdm+ with bases in the groove region of DNA is stronger than urea due to strong electrostatic interaction along with less self-aggregation of Gdm+ than urea. The distinct hydrogen bonding capability of Gdm+ and urea with DNA bases in its groove region affects its width differently. The interaction of Gdm+ decreases the width of the minor and major groove which probably increases the strength of hydrogen bond between the Watson-Crick base pairs of DNA leading to its stability. In contrast, the interaction of urea does not affect much to the width of the grooves except the marginal increase in the minor groove width which probably decreases the strength of hydrogen bond between Watson Crick base pairs leading to the destabilization of DNA. Our study clearly depicts the role of hydrogen bonding between DNA bases and denaturants in their stability and structural change which can be used further for designing of the guanidinium based drug molecules. [Display omitted] •GdmCl and urea intrude into groove region of DNA by striping surrounding water•The hydrogen bonding pattern of Gdm+ and urea with DNA bases in its groove region is multimodal and distinctly different from each other.•The interaction of Gdm+ decreases the width of the minor and major groove of DNA.•The interaction of urea marginally increase the minor groove width of DNA